The Impact of Environmental, Social, and Governance Performance on Financial Performance: Evidence from Industrial Sector Companies in ASEAN - Rahel Ananda Sitorus; Wahyu Widarjo (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study investigates the impact of Environmental Performance (EP), Social Performance (SP), and Governance Performance (GP) on the financial performance of industrial sector companies in five ASEAN countries during the period 2020–2024. Financial performance is measured using Return on Assets (ROA), while ESG dimensions are represented by environmental, social, and governance performance indicators. The study employs a quantitative approach using panel data regression analysis with the Fixed Effect Model (FEM) based on 261 firm-year observations. The findings reveal that Environmental Performance has a significant positive effect on financial performance, indicating that firms with stronger environmental practices tend to achieve higher profitability. Specifically, EP demonstrates a positive and statistically significant coefficient (β = 0.731, p = 0.016). In contrast, Social Performance and Governance Performance do not show significant effects on ROA, suggesting that these dimensions have not yet translated into measurable financial benefits within the observed period. Among the control variables, Growth Opportunity emerges as the most influential factor affecting financial performance (β = 6.881, p = 0.001). Furthermore, the model explains 71.96% of the variation in ROA, indicating strong explanatory power. Overall, the results suggest that in the context of ASEAN emerging markets, environmental performance plays a more important role in enhancing firm profitability than social and governance performance, highlighting the strategic value of environmental sustainability initiatives.